Gender, education, and cohort differences in healthy working life expectancy at age 50 years in Australia: a longitudinal analysis - Hambisa, Mitiku Teshome; Tawiah, Richard; Jagger, Carol; Kiely, K M (My University, 2023)
We aimed to estimate healthy working life expectancy (HWLE) at age 50 years by gender, cohort, and level of education in Australia. We analysed data from two nationally representative cohorts in the Household Income and Labour Dynamics in Australia survey. Each cohort was followed up annually from 2001 to 2010 and from 2011 to 2020. Poor health was defined by a self-reported, limiting, long-term health condition. Work was defined by current employment status. HWLEs were estimated with Interpolated Markov Chain multi-state modelling. We included data from 4951 participants in the cohort from 2001 to 2010 (2605 [53%] women and 2346 [47%] men; age range 50-100 years) and 6589 participants in the cohort from 2011 to 2020 (3518 [53%] women and 3071 [47%] men; age range 50-100 years). Baseline characteristics were similar between groups. Working life expectancy increased over time for all groups, regardless of gender or educational attainment. However, health expectancies only increased for men and people of either gender with higher education. Years working in good health at age 50 years for men were 9·9 years in 2001 (95% CI 9·3-10·4) and 10·8 years (10·4-11·3) in 2011. The corresponding HWLEs for women were 7·9 years (7·3-8·5) and 9·0 years (8·5-9·6). For people with low education level, HWLE was 7·9 years (7·3-8·5) in 2001 and 8·4 years (7·9-8·9) in 2011, and for those with high education level, HWLE rose from 9·6 years in 2001 (9·1-10·1) to 10·5 years in 2011 (10·2-10·9). Across all groups, there were at least 2·5 years working in poor health and 6·7 years not working in good health. Increases in length of working life have not been accompanied by similar gains in healthy life expectancy for women or people of any gender with low education, and it is not unusual for workers older than 50 years to work with long-term health limitations. Strategies to achieve longer working lives should address life-course inequalities in health and encourage businesses and organisations to recruit, train, and retain mature-age workers. Australian Research Council.
Lancet Public Health
Keywords: Ageing; Health and wellbeing